2012
DOI: 10.1108/02756661211282795
|View full text |Cite
|
Sign up to set email alerts
|

Innovation in small business: comparing face‐to‐face with virtual networking

Abstract: PurposeThe paper aims to better understand the process of networking by small business with their customers to achieve innovations. In particular the relative roles of face‐to‐face and virtual interaction are to be investigated.Design/methodology/approachInitially a week of participant observation was undertaken then 17 in‐depth interviews were conducted and analyzed. The biotechnology sector was used for the sample.FindingsNetworking interaction could be categorized into stages. A deepening of the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
2
7
0
3
Order By: Relevance
“…The conditions of the teams were still informal, where technological equipment was not as yet satisfactory to support mature level virtual interaction (Friedrich, 2017). So, from this, face-to-face interaction was needed to reduce limitations (Andres, 2002;Blenke, 2013;Hardwick et al, 2012;Kirkman et al, 2004). Mixed virtual interaction occurred during the pandemic, because of the spread of the virus, caused by human networks, brought about the necessity for communicational alternatives in businesses.…”
Section: Definisimentioning
confidence: 99%
See 2 more Smart Citations
“…The conditions of the teams were still informal, where technological equipment was not as yet satisfactory to support mature level virtual interaction (Friedrich, 2017). So, from this, face-to-face interaction was needed to reduce limitations (Andres, 2002;Blenke, 2013;Hardwick et al, 2012;Kirkman et al, 2004). Mixed virtual interaction occurred during the pandemic, because of the spread of the virus, caused by human networks, brought about the necessity for communicational alternatives in businesses.…”
Section: Definisimentioning
confidence: 99%
“…Kondisi tim masih informal, ketika perangkat teknologi belum memadai untuk mendukung interaksi virtual yang matang (Friedrich, 2017). Maka dari itu, interaksi tatap muka diperlukan untuk mengurangi keterbatasan (Andres, 2002;Blenke, 2013;Hardwick et al, 2012;Kirkman et al, 2004). Mixed virtual umum terjadi di masa pandemi, karena penyebaran virus yang disebabkan oleh jaringan manusia menyebabkan perlunya alternatif komunikasi dalam bisnis.…”
Section: Definisiunclassified
See 1 more Smart Citation
“…Furthermore, besides focusing on entrepreneurial orientation, innovation activities are more specific approaches that companies must do in order to increase competitive advantage [22]. Innovation is the key to maintaining a competitive advantage by combining knowledge with making new products [23]. Innovation can also include the use of the latest technology or implementing new ways in the company's production processes in competition in the same market, where entrepreneurs make innovative steps even though the company still faces the same competitors and struggles on the same market scale.…”
Section: Literature Review: Important Role Of Entrepreneurial Orientamentioning
confidence: 99%
“…can be answered by stating that they are open to knowledge, and that this knowledge is critical for growth, survival and innovation. Specifically in terms of innovation, Hardwick et al (2012) and demonstrated how small firms can co-create new knowledge for innovation by combining and synthesising tacit and codified knowledge to create new products and services. Moreover, Harbi (2011) and Anderson, Harbi and Amamou (2012) showed that when firms were not able to be open to new knowledge, innovation was very difficult indeed.…”
Section: Insert Figure 1 About Herementioning
confidence: 99%